Handwriting Kinematics in Patients with Schizophrenia Treated with Long-Acting Injectable Atypical Antipsychotics: Results From the ALPINE Study. Issue 1 (7th March 2022) - Caligiuri, Michael P; Weiden, Peter J; Legedza, Anna; Yagoda, Sergey; Claxton, Amy
Abstract: Handwriting kinematics (HWKs) were assessed in the randomized controlled ALPINE study of 2 long-acting injectable antipsychotics started during an acute exacerbation of schizophrenia. This exploratory analysis examined the relationship between baseline HWKs and response to acute antipsychotic treatment. Adults with acute schizophrenia were assigned to aripiprazole lauroxil or paliperidone palmitate (groups combined for this analysis). Treatment response was defined as ≥20% reduction from baseline in Positive and Negative Syndrome Scale (PANSS) total score at week 4. Two HWK measures, peak velocity (decreases with greater dysfunction) and percentage of nonballistic movements (%NBM; increases with greater dysfunction), were captured in 4 handwriting tasks (complex loops, maximum speed circles, overlay circles, and left-right loops). Peak velocity and %NBM at baseline were compared between responders and nonresponders. The analysis included 143 patients (mean baseline PANSS total score, 94.5). PANSS responders ( n = 67 [46.9%]) had a lower mean peak velocity (i.e., slower pen movements) on all HWK tasks at baseline compared with nonresponders ( n = 76): complex loops, 8.8 versus 12.1 cm/s; maximum speed circles, 18.0 versus 23.7 cm/s; overlay circles, 12.6 versus 17.2 cm/s; and left-right loops, 11.2 versus 14.6 cm/s. PANSS responders had a greater %NBM on 3 tasks compared with nonresponders: complex loops, 57.1% versus 47.4%; overlay circles, 30.6% versus 24.3%; and left-right loops, 58.7% versus 47.0%. In this exploratory analysis, PANSS responders to aripiprazole lauroxil or paliperidone palmitate treatment at week 4 had lower baseline HWK movement velocities and greater baseline %NBM versus nonresponders, suggesting that baseline HWKs might predict response to these antipsychotic drugs.